Identifying the key technical aspects of rugby place kicking: a qualitative case study of an elite coach - Bezodis, N. E.; Winter, S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Place kicking plays an important role in the outcome of rugby union matches. However, the understanding of rugby place kicking technique is currently limited and this study aimed to start `bridging the gap` between contemporary coaching expertise and the biomechanical understanding of rugby place kicking. An Interpretive Phenomenological Analysis of a semi-structured interview with an elite kicking coach was used to identify the key technical features of rugby place kicking and thus provide direction for future biomechanical research. Ball placement, the approach, body position at support leg contact, support leg mechanics, the path of the foot during the kicking phase and its orientation at ball contact, energy dissipation during the follow through, and overriding coordination issues were all identified as key areas in need of future research.